»Moderne Kunst« in Taiwan: Betrachtung eines Topos im Kontext der Globalisierung des Kunstdiskurses - Bauer-Zhao, Lisa (transcript, 2020)
What is "modern art"? The question is pursued from a Taiwanese perspective, thus questioning the Eurocentric narrative of modern art history.